“Do it All by Myself”: A Salutogenic Approach of Masculine Health Practice Among Farming Men Coping With Stress - Philippe Roy PhD; Gilles Tremblay PhD, SW; Steven Robertson PhD, RN; Janie Houle PhD (American Journal of Men's Health, 2017)
Farming is often considered one of the most stressful occupations. At the same time, farming men symbolically represent a strong, traditional, or hegemonic form of masculinity based on stoicism, resourcefulness, and resilience to adversity. A contrast is observed between this social representation and their health status, marked by higher levels of stress, social isolation, psychological distress, and suicide than many other subgroups of men. A salutogenic approach was taken in this study to enable the investigation of the social contexts in which farming men positively engage in health-promoting behaviors that may prevent or ameliorate mental health problems. A focus was placed on how farming men cope with stress on their own, and the relationship of this to their popular image of being resourceful and resilient. Thirty-two individual in-depth interviews with farming men and a focus group with five key informants working in rural areas within the Province of Quebec, Canada, were carried out. Self-distraction and cognitive strategies emerged as the most relevant for participants. Notably, taking work breaks conflicted with the discourse of the “relentless worker” that farmers are expected to be. Pathways to positive coping and recovery implied an ambivalence between contemplation of strategies aligned with negative aspects of traditional masculinity norms in North America and strategies aligned with more positive, progressive aspects of these norms based on the importance of family and work life balance. Health promotion and future research should investigate how various positive masculine practices can be aligned with farmers’ health and well-being and that of their family.